2015
DOI: 10.1074/jbc.m114.603118
|View full text |Cite
|
Sign up to set email alerts
|

Internal Dynamics of Dynactin CAP-Gly Is Regulated by Microtubules and Plus End Tracking Protein EB1

Abstract: Background:The role of microtubules on conformational dynamics of microtubule-associated proteins remains poorly understood. Results: Magic angle spinning NMR studies indicate significant differences in the dynamics of CAP-Gly going from the unbound to the MT-bound or EB1-bound state. Conclusion: Environment-dependent motions occurring on multiple time scales are functionally (biologically) relevant. Significance: Conformational dynamics of a MT-associated protein bound to microtubules at atomic resolution is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Furthermore, owing to its flexibility the CAP-Gly domain and the entire dynactin's shoulder projection are not visible in the high-resolution EM maps of the dynactin complex (21), precluding their structural analysis. Indeed, as we reported recently (24), CAP-Gly(19-107) bound to polymeric MTs is dynamic on the timescales spanning nano-to milliseconds, and the lack of electron density in the cryo-EM studies is consistent with our results. In contrast to the EM-based studies, MAS NMR experiments permit detection of dynamic complexes, as shown in our current work.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Furthermore, owing to its flexibility the CAP-Gly domain and the entire dynactin's shoulder projection are not visible in the high-resolution EM maps of the dynactin complex (21), precluding their structural analysis. Indeed, as we reported recently (24), CAP-Gly(19-107) bound to polymeric MTs is dynamic on the timescales spanning nano-to milliseconds, and the lack of electron density in the cryo-EM studies is consistent with our results. In contrast to the EM-based studies, MAS NMR experiments permit detection of dynamic complexes, as shown in our current work.…”
Section: Discussionsupporting
confidence: 81%
“…occurring over six decades of motional timescales (nano-to milliseconds), in its free form, assembled on MTs, and bound to EB1 (24). We discovered that loop regions of CAP-Gly are dynamic when both free and bound to MTs whereas their mobility is attenuated in complex with EB1.…”
Section: Significancementioning
confidence: 90%
See 3 more Smart Citations